Gender aspects of smallholder private groundwater irrigation in Ghana and Zambia - van Koppen, Barbara; Hope, L.; Colenbrander, W. (2023)
This paper explores gender aspects of smallholders’ private technology adoption for groundwater irrigation in Ghana and Zambia. It focuses on two variables of quantitative farm-household surveys: household headship and gendered plot management. The paper compares adoption rates and types of technologies for female- and male-headed households; examines adoption rates when women have their own plots; and compares women’s decision making on irrigated plots and rainfed plots. The findings suggest that there are largely untapped synergies between gender-equality and irrigation-policy goals. Systematic gender differentiation in surveys is recommended.